NURSING STUDENTS’ EXPERIENCE OF RECEIVING FEEDBACK IN CLINICAL LEARNING: A QUALITATIVE STUDY - Akhtar, Nasim; Kausar, Samina; Farooqi, Samina; Ghani, Mansoor (Journal of Postgraduate Medical Institute, 2021)
Objectives: To explore nursing students’ understanding of feedback, its timing and implementation in clinical learning with assessment of their perceived impact on performance due to feedback and barrier recognition. Methodology: This qualitative phenomenological study was conducted in College of Nursing, Allama Iqbal Medical College, Lahore and College of Nursing, Nishtar Medical University, Multan. Nursing students at level of bachelor were recruited using purposive sampling until data saturation. Data was collected through in-depth interviews of 28 participants. It was tape-recorded, transcribed and analyzed through thematic analysis framework method with inductive and deductive approach. Results: Eight themes were derived, namely; students’ understanding of feedback, feedback practices, categories of feedback provided, styles and occurrence of feedback, Components of feedback, effects of feedback on learners’ performance, perceived barriers to feedback practice, and areas for improvement in clinical supervision. Conclusion: Study revealed that in clinical setting infrequent and irregular feedback is provided to student which is not according to set criteria of evaluation of skills in clinical settings. Instructors focus on specific behaviours and are biased. Improper feedback and barriers to feedback hinder students’ learning.